Strategi Pengelolaan Berbasis Kawasan dalam Pemulihan Ekosistem Laut untuk Mendukung Pencapaian SDGs-14 - Isni Aini; Imbuk Risnawati; Islamul Hadi; Evy Aryanti (Jurnal Zona, 2026)
This study provides the role of area-based management in supporting marine ecosystem recovery and advancing the achievement of Sustainable Development Goal 14 (Life Below Water). Marine ecosystems deliver critical ecological and socio-economic services; however, escalating anthropogenic pressure including overfishing, habitat degradation, pollution, and climate change, have led to declining fisheries stocks and reduced ecosystem resilience. Employing a literature review approach with descriptive-analytical methods, this study critically analyzes the implementation, challenges, and effectiveness of ecosystem-based spatial management strategies. The findings reveal that the Ecosystem Approach to Fisheries Management (EAFM) constitutes a comprehensive framework that integrates ecological sustainability, socio-economic considerations, and governance structures. Its operationalization through instruments such as Marine Protected Areas (MPAs), Locally Managed Marine Areas (LMMAs), and Other Effective Area-Based Conservation Measures (OECMs) demonstrates considerable potential in restoring fish biomass, conserving habitats, and strengthening community-based resource management. Nevertheless, significant challenges persist including discrepancies between policy design and field implementation, weak cross-sectoral integration, inadequate monitoring and evaluation systems, low levels of compliance, and limited substantive community participation. Accordingly, this study underscores the importance of adopting integrative, adaptive, and collaborative management strategies. Strengthening ecosystem-based approaches, improving governance frameworks, enhancing stakeholder participation, advancing monitoring and evaluation mechanisms, and incorporating climate resilience are essential to ensure effective marine ecosystem recovery and the sustainability of coastal livelihoods